If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3u + 5(u + 3) = 5 Reorder the terms: -3u + 5(3 + u) = 5 -3u + (3 * 5 + u * 5) = 5 -3u + (15 + 5u) = 5 Reorder the terms: 15 + -3u + 5u = 5 Combine like terms: -3u + 5u = 2u 15 + 2u = 5 Solving 15 + 2u = 5 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 2u = 5 + -15 Combine like terms: 15 + -15 = 0 0 + 2u = 5 + -15 2u = 5 + -15 Combine like terms: 5 + -15 = -10 2u = -10 Divide each side by '2'. u = -5 Simplifying u = -5
| (3x^4-6x-5x^2+5)+(6x^2-4x^3-1+7x)= | | 8x-2/6=2x-5 | | 7(-9+x)=-49 | | t^3+2=12 | | 4.2-1.4=1.68-3.5x | | 2(-8-4)=72 | | 2(6x+1)=3x-5 | | 2(4x+2)=84 | | 3-4x=4+x | | e^3x=9 | | 5(5+3x)=160 | | 5+10+4p=9-5 | | 2r^2-2/3r | | 4(-2x+10)=48 | | (5x+8)(7+x)=0 | | 3x-5x+8x=48 | | 5y-y=-16 | | z^10/6 | | 1/3-m/21-1/7 | | -4(7+7x)=-280 | | 3.4-1.08=0.68-5.4x | | 0=2x-x | | -4+6x=4x+16 | | Y-3=-1/3(x-4) | | 14*8*5= | | 3+4y=8y-3 | | 4x^2+3x+42=0 | | n=-3+4x | | -4x+3-3x+2=5x+6 | | 5x+3=69-6x | | x^2-xy-4y^2=-2 | | y+9=5/4 |